PKM Kelompok UMKM Dodol Al-Barokah Dalam Inovasi Produk Pitadol Dan Eco Friendly Packaging Berbasis Limbah Pengrajin Bambu Di Bojonggede Bogor - Wawan Kurniawan; Ida Busnetty; Nur Aini; Ratna Yulika Go (Jurnal Pengabdian kepada Masyarakat Indonesia (JPKMI), 2023)
PKM Dodol Al-Barokah MSME Group in Product Innovation Pitadol and Eco Friendly Packaging Based on Bamboo Craftsmen's Waste in Bojonggede Bogor is an effort to improve the welfare of dodol makers which have existed since 1970. Partner problems are 1) they don't have new products (innovations). So far, only 4 flavors of dodol have been produced, 2) they still use plastic packaging. Plastic packaging materials besides damaging the environment also damage health, 3) partners experience difficulties in terms of capital. The solutions offered are 1) training on making a new dodol product called pitadol. Pitadol stands for banana, taro and dodol. Bananas and taro thrive in the Bojonggede area, 2) training on making packaging from bamboo craftsmen's waste (eco friendly packaging). Bamboo craftsmen in the Bojonggede Bogor area are more than 50 bamboo craftsmen. 3) Implementation of the perelek system, this system is a mutual cooperation system by collecting small change (coins) every Monday and Thursday collected from 25 group members. The funds from the perelek system will be given assistance to members who experience difficulties in terms of capital to buy production raw materials. The method is carried out by counseling, training and mentoring at each step of the activity. The activity was carried out with 4 students in the framework of MBKM activities. Students will receive recognition of 6 credits. The main performance indicators are IKU 2 and 5, while for lecturers IKU 5. The contribution of this service is the creation of a new product called Pitadol, the creation of environmentally friendly packaging products and the implementation of a perelek system which is an independent system in obtaining funds for group member capital.